2011
DOI: 10.1590/s0100-29452011000400002
|View full text |Cite
|
Sign up to set email alerts
|

Diquat e ureia no manejo da floração natural do abacaxizeiro 'Pérola'

Abstract: O florescimento natural do abacaxizeiro constitui-se num dos problemas mais sérios do seu manejo, devido à desuniformização e colheita em épocas impróprias, o que eleva o custo de produção e reduz o preço de venda. O objetivo deste trabalho foi avaliar o comportamento do diquat e da ureia como fitorreguladores no retardamento da diferenciação floral do abacaxizeiro cv. Pérola. Foram testadas as concentrações de 0; 15 mg L-1; 23 mg L-1; e 30 mg L-1 de diquat, sem e com ureia (20 g L-1), aplicando 50 mL-1 de cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Under natural conditions, pineapple flowering is slow and uneven, and occurs under conditions of short days and cold nights. To prevent this transition, from the vegetative to the reproductive phase, from occurring under inadequate conditions, the plants are induced to synchronize the floral differentiation by external ethylene treatments, a technique that allows to synchronize fruit formation and facilitate harvesting, in addition to being a strategy to stagger the production, so that the fruits are harvested at favorable times, when the supply of the product is scarce (Cunha, 2005;Kist et al, 2011).…”
Section: Management Floral Inductionmentioning
confidence: 99%
“…Under natural conditions, pineapple flowering is slow and uneven, and occurs under conditions of short days and cold nights. To prevent this transition, from the vegetative to the reproductive phase, from occurring under inadequate conditions, the plants are induced to synchronize the floral differentiation by external ethylene treatments, a technique that allows to synchronize fruit formation and facilitate harvesting, in addition to being a strategy to stagger the production, so that the fruits are harvested at favorable times, when the supply of the product is scarce (Cunha, 2005;Kist et al, 2011).…”
Section: Management Floral Inductionmentioning
confidence: 99%
“…(Cavatte et al 2012), acid lime trees (Citrus latifolia Tanaka cv. 'Tahiti') (Cruz et al 2009), pineapple (Ananas comosus) (Maruthasalan et al 2010, Kist et al 2011 and other ornamental species (Moraes et al 2012, Brescasin et al 2013. Despite the good results obtained with these other species, these products are not used in native fruits yet, especially in jabuticaba tree.…”
Section: Abstract Resumomentioning
confidence: 99%
“…It has been empirically observed that flowering occurs after pruning or continuous irrigation. Therefore, if bioregulators are correctly used, this may provide a longer period to fruit harvest, allowing the establishment of commercialization strategies, such as producing fruits off-season (Kist et al 2011), when the prices may reach higher values (Ataíde et al 2006). Given all that, this study aimed to evaluate the vegetative and reproductive behavior of hybrid jabuticaba tree under flowering induction in orchards.…”
Section: Abstract Resumomentioning
confidence: 99%
“…However, the varieties of A. comosus grown in these regions show slow growth during the vegetative growth phase (VGP), thereby prolonging the crop cycle, which can vary from 12 to 30 months until the first fruit is produced. The prolonged crop cycle affects production costs due to the need to control weeds, insect pests and diseases (PY et al, 1984;Catunda et al, 2005;Kist et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The VGP is considered one of the longest, ranging from 8 to 18 months. It is also considered the most important phase in the production cycle of the pineapple, as it is during this period that the plants acquire sufficient size for floral induction (natural or artificial), and the maximum nutritional reserve necessary for the development and quality of the fruit (Kist et al, 2011;Caetano et al, 2013;Franco et al, 2014). However, even when all the optimal growing conditions are provided, the pineapple shows slow growth during the VGP (Cuzzuol et al, 2005).…”
Section: Introductionmentioning
confidence: 99%